The problems and causes of match-fixing: are legal sports betting regimes to blame?. Issue 1 (12th March 2018) - Tak, Minhyeok; Sam, Michael P.; Jackson, Steven J.
Abstract : Purpose: Sport match-fixing has emerged as a complex global problem. The purpose of this paper is twofold. First, it critically reviews how match-fixing is typified as a policy problem. Second, it advances an analysis of the legal framework and regulatory system for sports betting as a causal source for "routinized" match-fixing. Design/methodology/approach: This study extracts and synthesises (cross-national) materials from policies, media releases and scholarly works on the subject of match-fixing and sports betting. The analysis is framed by the contrasts between rational choice and sociological institutionalist approaches. Findings: Match-fixing is typically attributed to: criminal organisations and illegal sports betting; vulnerable individuals; and failure of governance on the part of sports organisations. Each cause holds assumptions of utility-maximising actors and it is argued that due consideration be given to the fundamental risks inherent in legal sports betting regimes. Research limitations/implications: Match-fixing in sport is a recurrent social problem, transcending national boundaries and involving a wide range of actors and, sporting disciplines and levels of competition. Within such an environment, it may matter little how strong the incentive structures and education programmes are, when betting on human beings is both normatively and cognitively advanced as a value and institutionally permitted as a practice. Originality/value: This paper argues that legal betting regimes paradoxically contribute to routinised match-fixing because: for betting customers there is no qualitative, ethical difference between legal and illegal operators; and legalisation serves to normalise and legitimate the view of athletes as objects for betting (like cards or dice).